Exploring public perceptions of stratospheric sulfate injection - Merk, Christine; Pönitzsch, Gert; Braun, Carola; Rehdanz, Katrin; Schmidt, Ulrich (Climatic change, 2015)
Injecting sulfate aerosols into the stratosphere could quickly offset global warming caused by anthropogenic greenhouse gas emissions. Because the technology would have global side effects, it raises not only technological but also political, ethical, and social concerns. Therefore, research on sulfate injection should be accompanied by a global debate that incorporates public perceptions and concerns into the development and governance of the technology. Our paper provides insight into public perceptions and explores their underlying patterns using a survey conducted in Germany. The data reveal a differentiated picture. Laboratory research on sulfate injection is broadly approved, whereas field research is much less approved. Immediate deployment is largely rejected. The acceptance of the technology is associated with the belief that climate change is a serious problem and that humans will eventually be able to control nature. It is also determined by the levels of trust in scientists and firms. Among the strongest objections against the technology is the belief that humans should not manipulate nature in the way injecting sulfate would. The actual public perceptions of sulfate injection will, however, evolve along with the ongoing debate between the public, experts, and policymakers.